PENERAPAN MODEL PEMBELAJARAN TIPE MURDER UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS VII B SMPN 5 KOTA BENGKULU - NURITA NURITA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study aims to describe whether the MURDER Type Learning Model can improve the mathematical understanding ability of class VII B students of SMP Negeri 5 Bengkulu City. The research subjects consisted of 32 students of class VII B SMP Negeri 5 Bengkulu City. This research was motivated by the low interest, activity, and mathematical ability of class VII B students. Classroom action research was carried out in 2 cycles. The results of the analysis show that based on the results of the teacher's observation sheet in cycle I, it can be seen that the teacher's activities during the learning process are in the good category with an average score of 21.75. Teacher activity in cycle II increased by an average of 26.5 with good category. Meanwhile, student activities during the learning process in cycle 1 with an average value of 17 are included in the sufficient category. In the second cycle, student activity increased with an average value of 26.25 which was included in the good category. Mathematical understanding ability increased the number of students in the good category in the first cycle as many as 7 students (21.88%), in the second cycle increased to 28 students (87.50%). The number of students in the sufficient category in the first cycle were 21 students (65.63%), in the second cycle decreased to 4 students (12.50%), while in the less category in the first cycle as many as 4 students (12.50%), in the first cycle there were 4 students (12.50%). cycle II decreased to no students in the less category. Overall, the number of students in the good category has achieved a success indicator of > 65%, namely 87.50% (28 students). In cycle 1, the highest student score was 80 and the lowest student score was 40. While in cycle 2 the highest score was 95 while the lowest score was 75. It can be concluded that the success rate in cycle 1 has not been successful, while in cycle 2 it has been successful. This means that the MURDER type of learning model can improve the mathematical understanding ability of class VII B students of SMP Negeri 5 Bengkulu City. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan apakah Model Pembelajaran Tipe MURDER dapat meningkatkan kemampuan pemahaman matematis siswa kelas VII B SMP Negeri 5 Kota Bengkulu. Subjek penelitian terdiri dari 32 siswa kelas VII B SMP Negeri 5 Kota Bengkulu. Penelitian ini dilatar belakangi oleh rendahnya minat, keaktifan, dan kemampuan matematis siswa kelas VII B. Penelitian tindakan kelas dilaksanakan sebanyak 2 siklus. Hasil analisis menunjukkan bahwa berdasarkan hasil lembar observasi guru siklus I dapat diketahui bahwa aktivitas guru selama proses pembelajaran berada pada kategori baik dengan skor rata-rata sebesar 21,75. Aktivitas guru pada siklus II meningkat dengan rata-rata 26,5 dengan kategori baik. Sedangkan aktivitas siswa selama proses pembelajaran pada siklus 1 dengan nilai rata-rata 17 yang termasuk dalam kategori cukup. Pada siklus II aktivitas siswa meningkat dengan nilai rata-rata 26,25 yang masuk dalam kategori baik. Kemampuan pemahaman matematis mengalami peningkatan jumlah siswa dalam kategori baik pada siklus I sebanyak 7 siswa (21.88%), pada siklus II meningkat menjadi 28 siswa (87,50%). Jumlah siswa pada kategori cukup pada siklus I sebanyak 21 siswa (65,63%), pada siklus II menurun menjadi 4 siswa (12,50%), sedangkan pada kategori kurang pada siklus I sebanyak 4 siswa (12,50%), pada siklus II menurun menjadi tidak ada siswa yang dalam kategori kurang. Secara keseluruhan untuk jumlah siswa dalam kategori baik telah mencapai indikator keberhasilan (28 siswa). Pada siklus 1, nilai siswa tertinggi 80 dan nilai siswa terendah 40. Sedangkan pada siklus 2 nilai tertinggi 95 sedangkan nilai terendah 75. Dapat disimpulkan bahwa tingkat keberhasilan pada siklus 1 belum berhasil, sedangkan pada siklus 2 sudah berhasil. Hal ini berarti, bahwa Model Pembelajaran tipe MURDER dapat meningkatkan kemampuan pemahaman matematis siswa kelas VII B SMP Negeri 5 Kota Bengkulu.